Analyzing the Impact of Indonesian Financial Accounting Standards (IFAS) 71 on Allowance for Impairment Losses - Jauharotul Izzati; Mulyadi Soetardjo; Muchamad Irham Fathoni; Akbar Saputra (Jurnal Indonesia Sosial Teknologi, 2024)
This article analyzes the factors that impact allowance for impairment losses on banks in Indonesia, after the implementation of Indonesian Financial Accounting Standards (IFAS) 71. IFAS 71 became effective in 2020, replacing IFAS 55. IFAS 71 introduced several new methods for calculating the allowance for impairment losses. We collected data from conventional banks listed on the Indonesia Stock Exchange from 2016—2020. We created two models: the first will test the impact of several key factors like loans provided by banks, non-performing loans, and interest income towards allowance for impairment losses, while the second will test IFAS 71 implementation for these factors towards allowance for impairment losses. Out of these three factors, we concluded loans provided by banks hurt impairment loss allowance while the other two have a positive effect, regardless of IFAS 71 implementation. However, while this allowance is found to be higher after IFAS 71, the three key factors do not have a significantly stronger effect after IFAS 71 implementation